2020
DOI: 10.3390/nano10112236
|View full text |Cite
|
Sign up to set email alerts
|

From 2D to 3D Cancer Cell Models—The Enigmas of Drug Delivery Research

Abstract: Over the past decades, research has made impressive breakthroughs towards drug delivery systems, resulting in a wide range of multifunctional engineered nanoparticles with biomedical applications such as cancer therapy. Despite these significant advances, well-designed nanoparticles rarely reach the clinical stage. Promising results obtained in standard 2D cell culture systems often turn into disappointing outcomes in in vivo models. Although the overall majority of in vitro nanoparticle research is still perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 153 publications
0
62
0
Order By: Relevance
“…These data are consistent with the recent report, where the authors demonstrated the concentration-depended penetration of doxorubicin in spheroids [ 21 ]. Visually, there was no difference in penetration depth in stroma-rich spheroids, despite the general consideration of ECM as a physical barrier for NPs [ 5 , 22 , 23 ]. However, it is rather difficult to distinguish the differences between mono-and co-culture spheroids without the quantification analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These data are consistent with the recent report, where the authors demonstrated the concentration-depended penetration of doxorubicin in spheroids [ 21 ]. Visually, there was no difference in penetration depth in stroma-rich spheroids, despite the general consideration of ECM as a physical barrier for NPs [ 5 , 22 , 23 ]. However, it is rather difficult to distinguish the differences between mono-and co-culture spheroids without the quantification analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the mTHPC NPs, to date, only a limited number of NPs [ 10 ], preferably cyclodextrin-based [ 15 , 16 , 24 , 25 ], demonstrated the deep penetration in 3D cancer models. There is increasing evidence indicating that the physicochemical properties of NPs, such as size, charge, and surface chemistry, play a crucial role in their ability to penetrate ECM [ 5 , 6 , 26 ]. NPs tested in this study possess close physicochemical characteristics, ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations